Encryption, Privacy, and Usability : A Comparative Evaluation of Leading Secure Messaging Platforms - Ashish, Kumar; Bolisetty, Yaswanth; Singh, Deepanshu; Kaur, Amarinder (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This content provides an overview and analysis of popular messaging applications, focusing on encryption methods, security features, and usability. This work includes Signal, Telegram, WhatsApp, etc. By analyzing well-known platforms such as it evaluates usability and functionality while also evaluating their effectiveness in protecting user privacy. Key topics discussed include end-to-end encryption, encryption protocols, secure authentication methods, and preventing attacks such as man-in-the-middle and eavesdropping. Additionally, this content discusses issues and considerations related to secure messaging, including regulatory compliance, commercialization, and exchange cybersecurity threats. Combining current research and industry developments, it provides insight into the strengths and limitations of current messaging solutions as well as trending innovations in cryptography and privacy-enhancing techniques.
Keywords: Encryption; Privacy; Usability; Authentication; Secure Messaging; Encryption, Privacy; Security Features; End-To-End Encryption; Cryptographic Protocols; Digital Privacy; Communication Security; User Trust; Cybersecurity Threats; Regulatory Compliance; Eavesdropping